Local wisdom integration in science learning through culturally responsive teaching on students’ learning interests - Mardatila Mardatila; Mohammad Djamil M. Nur; Siti Rabiatul Adawiyah (STKIP Persada Khatulistiwa Sintang, 2026)
Science learning in schools still tends to be abstract and lacks a connection between the material and students' daily life contexts, resulting in low learning interest. This study is intended to investigate the influence of local wisdom-based science learning through the Culturally Responsive Teaching approach on students' learning interest. It is a quantitative study that has a quasi-experimental design and a non-equivalent control group design with 37 seventh-grade students of MTs. N 3 Parigi, a total of twenty participants were included in the experimental group, and seventeen participants were allocated to the control group. A Likert scale questionnaire with 16 validated statement items measured learning interest data, which were analyzed with the Mann-Whitney U test. The analysis showed that the experimental group achieved a greater mean rank of 23.45 than the control group of 13.76, and the observed difference was significant in statistical terms (p= 0.007, p < 0.05). Learning that connects science concepts with local cultural contexts makes learning more relevant and meaningful for students, thereby encouraging higher emotional and cognitive engagement. This study concludes that local wisdom-based science learning through the Culturally Responsive Teaching approach has a significant effect on students' learning interest.